Response to McGahan and Porter's commentary on ‘Industry, corporate and business‐segment effects and business performance: a non‐parametric approach’ - Ruefli, Timothy W.; Wiggins, Robert R. (Strategic Management Journal, 2005)
Abstract In the comment on Ruefli and Wiggins (2003), a number of points are made supporting the variance component analysis approach to determining the importance of industry, corporate, and business segment factors on business segment performance. This response addresses in more detail the nature of the methodological and statistical assumptions made by variance components analysis or ANOVA and their implications for the ‘puzzling’ results obtained when these techniques are employed. The response then contrasts the variance‐based methodologies with a non‐parametric approach used in Ruefli and Wiggins (2003) that makes fewer and weaker assumptions and yields more robust and more internally consistent results. The response also examines the limitations of employing an autoregressive approach to measuring persistence of abnormal profits and contrasts it with a non‐parametric methodology presented in the article. Copyright © 2005 John Wiley & Sons, Ltd.